Construction and Validation of Improved Triple Fusion Reporter Gene Vectors for Molecular Imaging of Living Subjects - Ray, Pritha; Tsien, Roger; Gambhir, Sanjiv Sam (Cancer research (Chicago, Ill.), 2007)
Multimodality imaging using several reporter genes and imaging technologies has become an increasingly important tool in determining the location(s), magnitude, and time variation of reporter gene expression in small animals. We have reported construction and validation of several triple fusion genes composed of a bioluminescent, a fluorescent, and a positron emission tomography (PET) reporter gene in cell culture and in living subjects. However, the bioluminescent and fluorescent components of fusion reporter proteins encoded by these vectors possess lesser activities when compared with the bioluminescent and fluorescent components of the nonfusions. In this study, we first created a mutant (mtfl) of a thermostable firefly luciferase (tfl) bearing the peroxisome localization signal to have greater cytoplasmic localization and improved access for its substrate, d-luciferin. Comparison between the three luciferases [mtfl, tfl, and firefly luciferase (fl)] both in cell culture and in living mice revealed that mtfl possessed 6- to 10-fold (in vitro) and 2-fold (in vivo) higher activity than fl. The improved version of the triple fusion vector carrying mtfl as the bioluminescent reporter component showed significantly (P < 0.05) higher bioluminescence than the previous triple fusion vectors. Of the three different red fluorescent reporter genes (jred, hcred, and mrfp1, isolated from jellyfish chromophore, coral Heteractis crispa, and coral Discosoma, respectively) evaluated, mrfp1 was able to preserve highest expression as a component of the triple fusion reporter gene for in vivo fluorescence imaging. A truncated version of wild-type herpes simplex virus 1 (HSV1) thymidine kinase gene (wttk) retained a higher expression level than the truncated mutant HSV1-sr39 TK (ttk) as the third reporter component of this improved triple fusion vector. Multimodality imaging of tumor-bearing mice using bioluminescence and microPET showed higher luciferase activity [(2.7 ± 0.1 versus 1.9 ± 0.1) × (106 p/s/cm2/sr)] but similar level of fluorine-18–labeled 2′-fluoro-2′-deoxyarabinofuranosyl-5-ethyluracil (18F-FEAU) uptake (1.37 ± 0.15 versus 1.37 ± 0.2) percentage injected dose per gram] by mtfl-mrfp1-wttk–expressing tumors compared with the fl-mrfp1-wttk–expressing tumors. Both tumors showed 4- to 5-fold higher accumulation (P < 0.05) of 18F-FEAU than fluorine-18–labeled 9-(4-fluoro-3-hydroxymethylbutyl)guanine. This improved triple fusion reporter vector will enable high sensitivity detection of lower numbers of cells from living animals using the combined bioluminescence, fluorescence, and microPET imaging techniques. [Cancer Res 2007;67(7):3085–93]